Pengaruh Dukungan Keluarga, Pemantauan Eksternal dan Motivasi terhadap Keberhasilan Studi Mahasiswa KIP-Kuliah - Siregar, Irma Hariyanti (Cattleya Darmaya Fortuna, 2024)
Higher education plays an important role in improving human capital and promoting economic and social development. However, accessibility to higher education can be hampered by economic barriers. Initiatives such as the KIP-Kuliah program in Indonesia aim to provide financial assistance to underprivileged students seeking higher education. This study aims to analyze the influence of family support, external monitoring, and motivation on the study success of KIP-Kuliah recipient students at Politeknik Ganesha Medan. This research uses a quantitative approach with a survey design. The study population was KIP-College recipient students, with a sample of 88 students selected by stratified random sampling. The research instrument was a questionnaire consisting of four main sections: family support, external monitoring, motivation, and study success. The validity and reliability of the instrument were tested using Pearson correlation and Cronbach alpha. Data analysis was conducted using descriptive and inferential statistical techniques, including Pearson correlation and multiple linear regression tests. The results showed that family support, external monitoring, and motivation significantly affect the success of student studies. Simultaneously, these three variables also contribute significantly to the academic success of students receiving KIP-Kuliah. Thus, this study emphasizes the importance of a holistic approach that includes financial, emotional, and academic support to improve student study success in higher education. The findings are expected to serve as a reference for the government, educational institutions, and families in developing more effective strategies to support underprivileged students.